Defining the practice of distal pancreatectomy around the world. Issue 10 (October 2019) - Maggino, Laura; Malleo, Giuseppe; Salvia, Roberto; Bassi, Claudio; Vollmer, Charles M.
Abstract: Background: Best management practices for distal pancreatectomy (DP) have not been conclusively defined. The aim of this study was to analyze the practice of DP worldwide and to compare surgeons' behavior with the best available evidence. Methods: A survey assessing management approaches for DP was distributed worldwide, in eight native-language translations. Regions were clustered: North-America, South/Central America, Asia/Australia, and Europe/Africa/Middle East. Results: Overall, 721/797 (91%) responding surgeons (median age = 48; years of experience = 14) indicated their region, representing six continents and 68 nations. Use of minimally-invasive (MI) techniques is diverse–highest in North-America (p < 0.001). Laparoscopy is the most common MI approach, while robotic techniques are rarely performed outside North-America. The preferred means of pancreatic remnant closure is via stapler – more commonly applied in North-America than in Europe/Africa/Middle East. Management techniques for the remnant and other fistula mitigation strategies display significant regional variability. The use of drains is also diverse, with the biggest disparity between North-American and Asian/Australian surgeons ( selective and routine drainers, respectively). Conclusion: There is wide heterogeneity in practices for DP worldwide, which is influenced by the surgeon's region of practice. Variability in practice reflects the lack of solid evidence on the benefit of any given strategy, underlining areas for improvement.